Sustained adenosine exposure causes endothelial mitochondrial dysfunction via equilibrative nucleoside transporters - Junsuk Ko; Sharon Rounds; Qing Lu (Pulmonary Circulation, 2020)
Adenosine is a potent signaling molecule that has paradoxical effects on lung diseases. We have previously demonstrated that sustained adenosine exposure by inhibition of adenosine degradation impairs lung endothelial barrier integrity and causes intrinsic apoptosis through equilibrative nucleoside transporter 1/2 -mediated intracellular adenosine signaling. In this study, we further demonstrated that sustained adenosine exposure increased mitochondrial reactive oxygen species and reduced mitochondrial respiration via equilibrative nucleoside transporter 1/2 , but not via adenosine receptor-mediated signaling. We have previously shown that sustained adenosine exposure activates p38 and c-Jun N-terminal kinases in mitochondria. Here, we show that activation of p38 and JNK partially contributed to sustained adenosine-induced mitochondrial reactive oxygen species production. We also found that sustained adenosine exposure promoted mitochondrial fission and increased mitophagy. Finally, mitochondria-targeted antioxidants prevented sustained adenosine exposure-induced mitochondrial fission and improved cell survival. Our results suggest that inhibition of equilibrative nucleoside transporter 1/2 and mitochondria-targeted antioxidants may be potential therapeutic approaches for lung diseases associated with sustained elevated adenosine.